Efektivitas Penggunaan Aplikasi Telegram Sebagai Media Menonton Mahasiswa Konsentrasi Broadcasting - Reksa, Mohammad Iqbal Maharansyah Arya; Wulandari, Dwi Rohma; Zainuddin, Sumarni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2024)
This study aims to determine the effectiveness of the telegram application as a medium for watching movies in meeting the needs and satisfaction of broadcasting concentration communication science students. By using the Uses and Gratification theory model. The research method used is descriptive quantitative with a questionnaire as a research instrument and data collection using the Simple Random Sampling technique. The population in this study were 116 Communication Science students with a broadcasting concentration who had been totaled from the class of 2019 and 2020. Data analysis in this study used quantitative descriptive data analysis. The results showed that as a medium for watching movies, the telegram application was effective in meeting the needs and satisfaction of broadcasting concentration communication science students with an average result of 2.88 which was calculated using the help of the SPSS version 26.0 statistical calculation application. The conclusion of this study is that the effectiveness of the telegram application of broadcasting concentration Communication Science students tends to be effective in meeting the needs and satisfaction as a medium for watching movies.